The model for successful development of NGA infrastructure in the Balkans - Požarnik, Matej; Robič Mohar, Lea; Taras, Tea (The European Journal of Applied Economics, 2016)
Unavailability of fast broadband internet access, primarily due to the lack of commercial interest of telecommunication operators, is the key reason for economic underdevelopment in rural areas in the Balkans. The process of developing broadband access in rural areas is multifaceted, complex and time-consuming. This paper analyses the current state of availability of broadband access in the Balkan countries, and investigates the algorithm with specific project phases and benefits of stakeholders at the national and local level. The purpose of the paper is to develop the model that rationalizes the implementation process of the broadband internet access projects, and to define the method of selecting an investment model for construction of broadband infrastructure. The results show that the Balkan countries have to start with preparatory activities and studies needed for successful implementation of the given model. This research contributes to stopping demographic and socio-economic degradation in less-developed areas, at the same time encouraging their development.